2019
DOI: 10.1103/physrevc.100.035207
|View full text |Cite
|
Sign up to set email alerts
|

Pure spin-3/2 representation with consistent interactions

Abstract: We have investigated the use of pure spin-3/2 propagator with consistent interaction Lagrangians to describe the property of spin-3/2 resonance. For this purpose we use the antisymmetric tensor spinor representation. By using the primary and secondary constraints we obtain the interaction fields that have the correct degrees of freedom. To visualize the result we calculate the contribution of spin-3/2 ∆ resonance to the total cross section of pion scattering and pion photoproduction off the nucleon. The result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This is understandable because the resonance masses used in the present analysis are below 2.3 GeV. However, this asymmetrical suppression is required for the covariant description of a resonance due to the large contribution of a Z-diagram that indicates the existence of a particle and an antiparticle in the intermediate state [35]. This contribution increases quickly as the energy of resonance increases beyond the resonance mass and, therefore, requires an increasing suppression.…”
Section: A General Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This is understandable because the resonance masses used in the present analysis are below 2.3 GeV. However, this asymmetrical suppression is required for the covariant description of a resonance due to the large contribution of a Z-diagram that indicates the existence of a particle and an antiparticle in the intermediate state [35]. This contribution increases quickly as the energy of resonance increases beyond the resonance mass and, therefore, requires an increasing suppression.…”
Section: A General Resultsmentioning
confidence: 89%
“…This contribution increases quickly as the energy of resonance increases beyond the resonance mass and, therefore, requires an increasing suppression. In our previous study [35] it was shown that the dipole form factor given by Eq. ( 18) is suitable for this purpose.…”
Section: A General Resultsmentioning
confidence: 98%
“…This fact has been often ignored in nuclear physics when computing the pion-nucleon interaction mediated by a spin-3/2 ∆ resonance [19][20][21][22][23][24], for instance, and in collider studies of generic spin-3/2 particles. There have been attempts to cure the problem by rewriting the interactions of the spin-3/2 fields [25][26][27][28][29][30][31][32][33][34][35][36][37]. Difficulties in formulating ∆-resonance interactions in a Lagrangian description have been discussed in ref.…”
Section: Jhep05(2021)254mentioning
confidence: 99%
“…Unfortunately, as explained above, the interacting Rarita-Schwinger field in the Lorentz representation (1, 1/2) contains unphysical degrees of freedom. In nuclear physics, where spin-3/2 resonances must be described, physicists avoid the extra degrees of freedom by using second-derivative Lagrangians with specifically chosen interactions to describe the (3/2, 0) representation [31][32][33]. We argue that, in this case, even the free field theory cannot be quantized consistently without introducing new fields and constraints (see Appendix B), despite the fact that the SM does admit the second-order formulation [34,35].…”
Section: Introductionmentioning
confidence: 99%